Building Financial Resilience for Local Food MSMEs Through Cost Adaptation, Cash Flow Stability, and Energy Efficiency - Nengsi Sudirman; Hardianti Pertiwi; Muh. Ramli; Arianto Dangkeng; Afrianto Afrianto (Economics and Digital Business Review, 2026)
This study aims to analyze the effects of cost adaptation, cash flow stability, and energy efficiency on the financial resilience of local food MSMEs. Financial resilience is a crucial aspect that enables MSMEs to cope with changing economic conditions, rising operational costs, and increasingly dynamic business competition. This study employed a quantitative approach, with the population consisting of all local food MSMEs in Palopo City. A total of 176 respondents were selected as the research sample. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that cash flow stability and energy efficiency have a positive and significant effect on financial resilience. In contrast, cost adaptation does not have a significant effect on financial resilience. These results suggest that the ability of MSMEs to maintain stable cash flow and manage energy consumption efficiently are key factors in strengthening their financial resilience. This study implies that MSME owners should improve financial management practices and operational efficiency to ensure business sustainability amid economic uncertainty.